P049 Barriers and facilitators to the delivery of insomnia management by general practice nurses: a qualitative analysis of patient perspectives. (9th November 2022) - Grivell, N; Hoon, E; Chai-Coetzer, C; Fuller, J; McEvoy, R
Abstract: Introduction: With insufficient providers of insomnia care, alternative approaches to the delivery of insomnia treatments are being explored. Research has demonstrated that insomnia can be successfully managed by primary care nurses but patient attitudes towards this care are largely unknown. This study explored patient perspectives towards barriers and facilitators to practice nurse-delivered care to inform the development of patient-centred models of care for insomnia. Methods: A qualitative sub-study within a process evaluation of sleep health care delivered in a pilot study in one general practice in metropolitan Adelaide. Semi-structured telephone interviews were conducted with patients with insomnia offered nurse-delivered or nurse-supported insomnia management. Thematic Analysis was used to identify themes within the data. Results: Eleven patients participated (6 males; age mean [range] 59 years [29-72]; time at practice 14.3 years [4-21]; Sleep Condition Indicator 9.5 [3-14]). Two major themes were identified: 1. Patients are supportive of nurses providing care for uncomplicated insomnia; 2. Trust in practice nurse-delivered insomnia care is influenced by relationships with the GP, the practice, and the nurse. Participants reported confidence in practice nurses providing insomnia management provided that they had sufficient knowledge. Established relationships with the GP and the practice, along with previous appointments with the nurse, increased patient confidence in nurse-delivered insomnia care. Discussion: Patient acceptance of practice nurse-delivered insomnia care supports further research into developing a role for practice nurses within insomnia management. The findings of this work will be tested and explored further within a large implementation study conducted in multiple general practices.